Carotid-Cavernous Fistula: Manifestasi Klinis dan Tatalaksana - Putri, Nadira Deanda; Prasetyo, Bambang Tri; Kurniawan, Ricky Gusanto; Rilianto, Beny; Windiani, Pratiwi Raissa; Arham, Abrar (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Carotid-cavernous fistula (CCF) is a vascular abnormality that occurs between the internal or external carotid artery and veins within the cavernous sinus. CCFs can be classified as direct (Barrow type A) or indirect CCFs (Barrow types B, C, and D). The causes of direct CCFs are trauma and vascular rupture, whereas indirect CCFs are commonly found in patients with hypertension, connective tissue disorders, pregnancy, and dissection of the internal carotid artery. Signs and symptoms of CCF vary widely, ranging from acute-onset headache, proptosis, diplopia, ophthalmoplegia, conjunctival chemosis, orbital bruit, and blindness, but it can solely manifest as conjunctival redness. Patients with suspected CCF should undergo neuroradiology imaging, followed by endovascular intervention to close the fistula and keep the carotid artery open. With appropriate treatment, complete resolution is expected to occur in all patients.